Эволюция генома и маркерная селекция растений - Сиволап, Ю.М. (Фактори експериментальної еволюції організмів, 2013)
Study variability and evolution of the genome is of great theoretical and practical significance. Plant breeding using the knowledge of the genome and genes to create a more productive and resistant varieties. The development of molecular genetics contributed to the creation of new technologies to increase the efficiency of the breeding process. In practice genetiics – breeding research have been implemented MAS and MAB technology, which can significantly reduce the scale of field plots and accelerate to select genotypes with the right combination of genes (alleles). Genetic markers of playing an important role in studying the genetic constitution of the varieties, and in particular, the evaluation of the initial selection of the material, because it easier to control the incorporation of genetic factors from parent forms produced varieties and hybrids. A pioneer and a development center in Ukraine marker technology was South Plant Biotechnology Center where developed and put into practice marking simple and quantitative agronomy valuable genes and the system of identification and registration crop varieties.

Key words: evolution, genome, plant breeding, marker, South Plant Biotechnology Center, Ukraine.